Morphological Variety in Distoseptispora and Introduction of Six Novel Species - Jing Yang (MDPI AG, 2021)
Distoseptispora is one of the sporidesmium-like taxa with great variation in asexual morphology and delineation of species. Phylogenetic analyses of four gene regions LSU, ITS, TEF1α, and RPB2 revealed the placement of several sporidesmium-like species in Distoseptispora (Distoseptisporaceae, Distoseptisporales, Sordariomycetes), collected on submerged decaying twigs from streams in China and Thailand. Based on morphological examination and molecular DNA data, six new species, Distoseptispora amniculi, D. atroviridis, D. effusa, D. fusiformis, D. hyalina, and D. verrucosa, are proposed. Among them, D. hyalina is the first sexual morph confirmed in the genus. A new geographical record is reported for D. lignicola in China. Conidial length proved to be of less taxonomic significance for some Distoseptispora species, whereas the type of conidial septa is informative at species level.